Nanoparticle surface charge detection method based on electrostatic interaction
Through electrostatic interaction in nanoparticle surface charge detection, the electrostatic interaction between liquid-based limited-domain porous materials and ionic surfactants is used to measure the pressure threshold changes, which solves the problem of expensive equipment and large errors in the prior art, and realizes the realization of the problem of achieving high-level errors. Low-cost, high-sensitivity nanoparticle surface charge detection.
Patent Information
- Application Number
- CN202411358381.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The existing nanoparticle surface charge detection methods rely on expensive instruments and equipment, have high detection costs and large measurement errors and uncertainties, and lack simple, easy to operate and high sensitivity detection methods.
The porous material is infiltrated by ionic surfactant solution to form a liquid-based limited-domain porous material. The pressure threshold of the transport fluid through the gated unit is changed by measuring the pressure threshold change, and the charge properties of the nanoparticles are determined by measuring the pressure threshold change. The linear simula The combined method obtains the charge amount.
It realizes high-sensitivity nanoparticles surface charge detection without complex equipment, is low-cost and is suitable for different types, sizes and forms of nanoparticles. It has a wide range of application, reduces detection errors, and has good safety and portability.
Smart Images

Figure CN119246384A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical fields of nanotechnology, material science and surface chemistry, and specifically relates to a method for detecting surface charge of nanoparticles based on electrostatic interaction. Background Art
[0002] The surface charge of nanoparticles is an important indicator for evaluating the stability and interaction of colloidal dispersions, and is also one of the important physical and chemical parameters in many fields such as chemical engineering, physics, materials, environment and biomedicine. The surface charge properties of nanoparticles not only affect the interaction between particles, but also affect their interaction with the surrounding medium or other substances. At present, the mutual repulsion or attraction between particles is often measured by detecting the Zeta potential (ζ-potential or ζ-potential) of nanoparticles. By measuring the Zeta potential, the dispersibility, surface charge and interfacial reaction process of nanoparticles can be understood. The change of this property is of great significance in many application fields. For example, in the design of cosmetic formulas, the dispersibility of nanoparticles can be optimized by adjusting the surface charge of particles, thereby improving the stability and performance of products; in the development of 3D printing materials, the control of particle surface charge helps to improve printing accuracy and material properties; in the mineral processing industry, the surface charge of particles is used to adjust the behavior of particles in the flotation process to improve the recovery rate of minerals. In addition, the study of particle surface charge also has important applications in the biomedical field (such as drug delivery and imaging technology), material preparation (such as coatings and composite materials), and environmental testing (such as water quality monitoring and pollutant removal).
[0003] At present, the commonly used methods for detecting the surface charge of nanoparticles mainly include electrophoretic light scattering, streaming potential, ultrasonic electroacoustic method and microelectrophoresis. Although these methods are widely used, they often rely on specific and expensive instruments and equipment, have high detection costs, and may face large measurement errors and uncertainties in actual operations. Based on this, the development of a simple, easy-to-operate, and highly accurate method for detecting the surface charge of nanoparticles has important scientific research and industrial application value. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for detecting the surface charge of nanoparticles based on electrostatic interaction. The method does not require complex instruments and equipment, has the characteristics of portability and high sensitivity, can accurately measure the surface charge properties of nanoparticles, and solves the problems of expensive detection and analysis methods and instruments and equipment and high cost of experimental methods in the above-mentioned background technology.
[0005] The technical solution adopted by the present invention to solve its technical problems is as follows: a method for detecting the surface charge of nanoparticles based on electrostatic interaction is provided, wherein a porous material is completely infiltrated with an ionic surfactant solution to form a liquid-based confined porous material, and nanoparticles to be tested are added to the liquid-based confined porous material to form a gating unit; the electrostatic interaction between the ionic surfactant and the nanoparticles to be tested in the liquid-based confined porous material is utilized to increase or decrease the pressure threshold of the transport fluid through the gating unit; the surface charge properties of the nanoparticles to be tested are determined by measuring the change in the pressure threshold, and the charge amount of the nanoparticles to be tested is obtained by a linear fitting method.
[0006] Optionally, the ionic surfactant solution includes cationic surfactants, anionic surfactants, zwitterionic surfactant aqueous solutions, and responsive ionic surfactants, and the concentration range is 0.1 to 2CMC (CMC is the critical micelle concentration of the surfactant).
[0007] Optionally, the cationic surfactant includes cetyltrimethylammonium bromide (CTAB), and the anionic surfactant includes sodium dodecyl sulfate (SDS).
[0008] Optionally, the porous material includes one of a nylon porous membrane, an aqueous mixed cellulose membrane, a polytetrafluoroethylene membrane, a polyvinylidene fluoride membrane, a porous glass membrane, and a metal porous membrane, and the pore size range of the pores is 5 to 50 μm.
[0009] Optionally, the nanoparticles to be tested are hydrophilic nanoparticles, including silicon dioxide, aluminum oxide, cerium dioxide, and silicon carbide. The nanoparticles to be tested use a polar solvent as a dispersion medium to form a test solution, and the mass fraction of the nanoparticles in the test solution ranges from 0.01 to 1.0 wt.%. The morphology of the nanoparticles includes but is not limited to spherical, rod-shaped, flake-shaped, cubic, and the like.
[0010] Optionally, the electrostatic interaction includes changes in surface tension, surface wettability, surface charge, pH value, viscosity or composition due to charge exchange of substances at the contact interface.
[0011] Optionally, the transport fluid is a gas, including air, oxygen, nitrogen, argon, carbon dioxide or carbon monoxide.
[0012] Optionally, when the pressure threshold is increased, the surface of the nanoparticle to be tested is judged to be negatively charged, and the linear model "charge = -21.01 (±1.15) △P-6.56 (±1.15)" is used to calculate the negative charge, where △P is the transmembrane pressure threshold change. When the pressure threshold is reduced, the surface of the nanoparticle to be tested is judged to be positively charged, and the linear model "charge = -61.54 (±2.44) △P + 2.10 (±1.23)" is used to calculate the positive charge, where △P is the transmembrane pressure threshold change.
[0013] Optionally, a detection system is used; the detection system includes a gas input channel, a gating unit, a gas output channel and a particle detection unit; the gating unit is arranged between the gas input channel and the gas output channel, the gating unit is provided with a chamber, the liquid-based confined porous material is encapsulated in the chamber, and the chamber is provided with a channel for injecting liquid to be tested; the particle detection unit includes a pressure sensor and a data conversion system, the pressure sensor is used to collect pressure information and input it into the data conversion system, and the data conversion system converts the pressure information and its change value into charge information on the surface of the nanoparticles.
[0014] Optionally, the detection method specifically includes the following steps:
[0015] 1) fully infiltrating the pores of the porous material with an ionic surfactant solution to prepare a liquid-based confined porous material, and encapsulating it in a chamber;
[0016] 2) dispersing the nanoparticles to be tested in a polar solvent to form a liquid to be tested, and injecting the liquid to be tested into the chamber through the liquid injection channel to cause electrostatic interaction at the liquid-base confined interface;
[0017] 3) The transport fluid is introduced from the gas input channel, and the changes in the critical transmembrane pressure are recorded and monitored by the pressure sensor of the particle detection unit. At the same time, the pressure threshold changes are converted into charge information on the particle surface using a data conversion system.
[0018] Optionally, in step 3), a constant flow rate of gas is passed into the chamber of the gate control unit, and the gate control unit can be opened by gradually increasing the gas pressure. The change of fluid pressure is monitored by a pressure detection device, and the surface charge information of the nanoparticles to be tested is obtained by a linear fitting method.
[0019] Compared with the background technology, this technical solution has the following advantages:
[0020] (1) This scheme uses the electrostatic interaction between ionic surfactants and nanoparticles at the liquid-based confined interface formed by the contact between the liquid to be tested and the porous membrane to design a simple, low-cost and highly sensitive nanoparticle surface charge detection system. By using the difference in the change of the critical pressure / pressure of the gas, the difference in the surface charge properties of the nanoparticles can be accurately measured.
[0021] 2) This scheme requires very little sample and can be tested at nanometer-level concentrations. It is low-cost and applicable to nanoparticles of different types, sizes, and forms. It has a wide range of applications and can save expensive or difficult-to-obtain nanomaterials.
[0022] 3) Compared with traditional detection technologies such as electrophoretic light scattering and streaming potential that rely on expensive and complex equipment, this scheme has a simple detection system structure, easy operation, and no need to control the application of high-voltage electric field. It has good safety and portability and is suitable for rapid on-site detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 a is a schematic diagram of the structure of the detection system of the embodiment, and b is a schematic diagram of the formation of the gating unit; wherein, 1-gas input channel, 2-(material support) chamber, 3-gating unit, 31-liquid-based confined porous material, 32-liquid to be tested, 4-gas output channel, 5-pressure sensor, 6-data conversion system, 7-injection channel of the liquid to be tested.
[0024] Figure 2 Schematic diagram of the nanoparticle surface charge detection principle of Example 1; wherein a and b are the mechanisms by which negatively charged and positively charged nanoparticles change the system pressure threshold through electrostatic interaction with CTAB molecules, respectively.
[0025] Figure 3 Schematic diagram of the relationship between the critical pressure threshold corresponding to different types of nanoparticles in Example 1 and the size of the particle surface charge.
[0026] Figure 4 This is a graph showing the relationship between different cationic surfactant CTAB concentrations and the change in transmembrane pressure threshold of the silica nanoparticle solution in Example 2.
[0027] Figure 5 This is a relationship diagram of the change in transmembrane pressure threshold corresponding to the silica nanoparticle solution under different pH conditions in Example 3.
[0028] Figure 6 This is a relationship diagram of the change in transmembrane pressure threshold corresponding to nanoparticle solutions of different concentrations in Example 4.
[0029] Figure 7 This is a relationship diagram of the changes in transmembrane pressure thresholds of the anionic surfactant SDS and different types of nanoparticles in Example 5. DETAILED DESCRIPTION
[0030] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments.
[0031] Figure 1a and b, a nanoparticle surface charge detection system based on electrostatic interaction includes a gas flow channel, a gating unit 3 and a particle detection unit; the gas flow channel includes a gas input channel 1, a functional channel and a gas output channel 4, the gas transport channel 1 and the gas output channel 4 are respectively arranged on the opposite sides of the gating unit and are connected through the functional channel, and the gas flow channel is connected with a pressure sensor 5; the gating unit 3 is arranged in the gas flow channel, including a liquid-based confined porous material 31, the liquid-based confined porous material 31 is formed by completely infiltrating the porous material with an ionic surfactant, and is encapsulated in a material support chamber 2, and a test liquid 32 containing hydrophilic nanoparticles is added to the liquid-based confined porous material 31 in the material support chamber 2 through a test liquid injection channel 7, and the electrostatic interaction between the two generates a response to form a functional channel of the gas flow channel; the particle detection unit includes a pressure sensor 5 and a data conversion system 6.
[0032] A transport fluid (i.e., gas) with a certain pressure is introduced into the gas input channel 1, and the gate unit can be opened by gradually increasing the pressure of the gas. After the gas passes through the gate unit, the pressure sensor 5 records the maximum pressure reading in the gas output channel 3. The data conversion unit 6 converts the pressure drop into the particle surface charge information based on the difference between the two maximum pressure readings recorded before and after the addition of the test liquid.
[0033] The principle of the method for detecting the surface charge of nanoparticles of the present invention is as follows Figure 2 As shown, the gate control unit 3 contains ionic surfactant molecules with charged head groups and hydrophilic nanoparticles with charged surfaces. The hydrophilic nanoparticles with charged surfaces will have an electrostatic attraction with the surfactant molecules with opposite charges. While reducing the surfactant molecules adsorbed on the gas-liquid interface, a nanoparticle-surfactant molecule complex with certain surface activity is formed and stably adsorbed on the gas-liquid interface, forming a physical barrier when the gas is passed, thereby increasing the critical transmembrane pressure when the gas passes through; for surfactant molecules with the same charge, the nanoparticles in the liquid and the ionic surfactant molecules with the same charge have an electrostatic repulsion, so that the surfactant molecules originally distributed in the liquid are also adsorbed to the gas-liquid interface, increasing the number and density of adsorption on the interface, reducing the surface tension of the liquid, and thus reducing the critical transmembrane pressure when the gas passes through. After the gas opens the gate control unit 3, it enters the gas output channel 4, and the pressure sensor 5 detects and records the maximum pressure indication at this time (the area of the porous material is known, and the maximum pressure indication can be calculated). According to the change in indication before and after the addition of the liquid to be tested, the data conversion system 6 can obtain the electrical and electrical information of the nanoparticles to be tested.
[0034] Example 1
[0035] refer to Figure 2 a, with Figure 1The system structure shown is used as the basis to detect the charge size of different types of nanoparticles. A cationic surfactant hexadecyltrimethylammonium bromide solution (CTAB, concentration 0.1mM, i.e., the critical micelle concentration of the surfactant is 0.1CMC) is selected to completely infiltrate a hydrophilic nylon filter (pore size 10μm, much larger than the particle size) to prepare a liquid-based confined porous material. After being placed in the access control unit, the device is sealed and air is selected as the transmission fluid to pass through the gas input channel (constant flow rate: 2mL / min), and the initial transmembrane pressure P0 of the test system is tested. An aqueous dispersion of negatively charged particles (all with a concentration of 0.1wt.%), such as silica nanoparticles, is selected as the liquid to be tested. After the liquid to be tested is injected into the access control unit through the liquid injection channel 7, the device is sealed and air is selected as the transmission fluid to pass through the gas input channel. When the gas pushes the liquid film in the pore, as Figure 2 As shown in a, the negatively charged nanoparticle-CTAB complex will form a physical barrier at the gas-liquid interface to block the further entry of gas, causing the transmembrane pressure to increase to P1. According to the DLVO theory, negatively charged nanoparticles with a larger surface charge have a stronger electrostatic attraction to CTAB molecules, and can form a more uniform and dense particle layer at the gas-liquid interface, resulting in a higher transmembrane pressure in the system. Figure 3 As shown in a, if the critical pressure threshold of the gating unit after adding the test liquid is greater than the initially measured pressure threshold (P1>P0), it can be judged that the particle surface is negatively charged; by detecting the transmembrane pressure change between different negatively charged nanoparticles and the initial gating unit (ΔP=P1-P0), the surface charge of the particles can be determined.
[0036] Example 2
[0037] refer to Figure 2 b, with Figure 1 The system structure shown is used as a basis to detect the charge size of different types of nanoparticles. A cationic surfactant hexadecyltrimethylammonium bromide solution (CTAB, concentration 0.1mM) is selected to completely infiltrate a hydrophilic nylon filter (pore size 10μm, much larger than the particle size) to prepare a liquid-based confined porous material. After being placed in the access control unit, the device is sealed and air is selected as the transmission fluid to pass through the gas input channel (constant flow rate: 2mL / min), and the initial transmembrane pressure P0 of the test system is tested. An aqueous dispersion of positively charged particles (all with a concentration of 0.1wt.%), such as aluminum oxide nanoparticles, is selected as the liquid to be tested. After the liquid to be tested is injected into the access control unit through the liquid injection channel 7, the device is sealed and air is selected as the transmission fluid to pass through the gas input channel. As shown Figure 2As shown in Figure b, positively charged nanoparticles will not form electrostatic complexes with CTAB, but will allow some CTAB molecules dispersed in the liquid to enter the gas-liquid interface through electrostatic repulsion, making the arrangement of CTAB molecules at the gas-liquid interface more uniform and compact, thereby reducing the surface tension of the liquid and reducing the transmembrane pressure to P2. The larger the surface charge of positively charged nanoparticles, the greater the electrostatic repulsion they produce on CTAB molecules, and the more the system transmembrane pressure is reduced. Figure 3 As shown in a, if the critical pressure threshold of the gating unit after adding the test liquid is less than the initially measured pressure threshold (P2<P0), it can be judged that the particle surface is positively charged; by detecting the transmembrane pressure change between different positively charged nanoparticles and the initial gating unit (ΔP=P2-P0), the surface charge of the particles can be determined.
[0038] Example 3
[0039] Cationic surfactant hexadecyltrimethylammonium bromide solutions of different concentrations (0.001mM, 0.01mM, 0.1mM, 1.0mM, 10mM) were selected to completely infiltrate a hydrophilic nylon filter (pore size 10μm, much larger than the particle size) to prepare a liquid-based confined porous material. After being placed in the access control unit, the device is sealed and air is selected as the transmission fluid to pass through the gas input channel (constant flow rate: 2mL / min), and the initial transmembrane pressure P0 of the test system is tested. A water dispersion of silica nanoparticles (concentration of 0.1wt.%) is selected as the liquid to be tested. After the liquid to be tested is injected into the access control unit through the liquid injection channel 7, the device is sealed and air is selected as the transmission fluid to pass through the gas input channel, and the transmembrane pressure change of the test system is tested. Figure 4 As shown in the figure, the transmembrane pressure of the system after adding the nanoparticles to be tested has a tendency to first increase and then decrease as the CTAB concentration increases, wherein the CTAB molecules exceeding the critical micelle concentration (CMC) have a tendency to spontaneously form micelles and multilayer adsorption on the particle surface, thereby allowing the surface-active nanoparticle-CTAB complex at the gas-liquid interface to re-enter the liquid interior, and at the same time, the excess CTAB molecules will compete with it for adsorption at the gas-liquid interface, reducing the strength of the physical barrier formed and reducing the transmembrane pressure.
[0040] Example 4
[0041] A cationic surfactant hexadecyltrimethylammonium bromide solution was selected to completely infiltrate a hydrophilic nylon filter (pore size 10 μm, much larger than the particle size) to prepare a liquid-based confined porous material. After being placed in the access control unit, the device was sealed and air was selected as the transmission fluid to pass through the gas input channel (constant flow rate: 2 mL / min), and the initial transmembrane pressure P0 of the system was tested. Aqueous dispersions of silica nanoparticles (all with a concentration of 0.1 wt.%) with different pH values (pH = 3, 5, 7, 9, 11) were selected as the liquids to be tested. After the liquids to be tested were injected into the access control unit through the liquid injection channel 7, the device was sealed and air was selected as the transmission fluid to pass through the gas input channel to test the transmembrane pressure change of the system. Figure 5 As shown in the figure, the surface charge of nanoparticles in aqueous solution is related to the dissociation behavior of their surface functional groups. In an acidic environment (pH < 7), due to the presence of more protons (H+), the silica nanoparticles carry less negative charge; in an alkaline environment (pH > 7), the OH- in the solution can promote the deprotonation of the surface groups of the silica nanoparticles, thereby increasing the negative charge on the particle surface. Figure 5 As shown in the figure, as the pH value increases from low to high, the transmembrane pressure of the system increases gradually, which is consistent with the change trend of the particle zeta potential.
[0042] Example 5
[0043] A cationic surfactant hexadecyltrimethylammonium bromide solution is selected to completely infiltrate a hydrophilic nylon filter (pore size 10μm, much larger than the particle size) to prepare a liquid-based confined porous material. After being placed in the access control unit, the device is sealed and air is selected as the transmission fluid to pass through the gas input channel (constant flow rate: 2mL / min), and the initial transmembrane pressure P0 of the test system is tested. Aqueous dispersions of different silica and aluminum oxide nanoparticle concentrations (0.01%, 0.05%, 0.1%, 0.5%, 1.0%) are selected as the liquids to be tested. After the liquids to be tested are injected into the access control unit through the liquid injection channel 7, the device is sealed and air is selected as the transmission fluid to pass through the gas input channel to test the transmembrane pressure change of the system. Figure 6 As shown in the figure, the change of the transmembrane pressure of the system increases with the increase of nanoparticle concentration, and the increasing trend increases sharply after exceeding 0.5wt.%. After the nanoparticles combine with CTAB molecules, if the particle concentration is too low, the gas-liquid interface will be insufficiently covered, resulting in poor system stability; if the particle concentration is too high, it will cause agglomeration and system blockage, mutual shielding, increase detection errors and control difficulties.
[0044] Example 6
[0045] An anionic surfactant, sodium dodecyl sulfate (SDS) (concentration 1.0 mM, i.e. 0.1 CMC) was selected to completely infiltrate a hydrophilic nylon filter with a pore size of 10 μm, much larger than the particle size) to prepare a liquid-based confined porous material. After being placed in the access control unit, the device is sealed and air is selected as the transmission fluid to pass through the gas input channel (constant flow rate: 2 mL / min), and the initial transmembrane pressure P0 of the test system is tested. Aqueous dispersions of silica, copper oxide, aluminum oxide, and titanium oxide nanoparticles (all with a concentration of 0.1 wt.%) were selected as the test liquids. After the test liquids were injected into the access control unit through the test liquid injection channel 7, the device was sealed and air was selected as the transmission fluid to pass through the gas input channel, and the transmembrane pressure change of the test system was tested. Unlike the positively charged head group of CTAB molecules, the head group of SDS molecules is negatively charged, so the adsorption / repulsion mode is opposite to that of charged nanoparticles. As Figure 7 As shown in the figure, for negatively charged silicon dioxide and copper oxide nanoparticles, the transmembrane pressure difference of the system is less than 0, and for positively charged aluminum oxide and titanium oxide nanoparticles, the transmembrane pressure difference of the system is greater than 0, and is consistent with the trend of particle zeta potential changes. This system realizes the versatility of detecting the surface charge of nanoparticles using different ionic surfactants at low concentrations.
[0046] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for detecting surface charge of nanoparticles based on electrostatic interaction, characterized in that: A liquid-based confined porous material is formed by completely infiltrating the porous material with an ionic surfactant solution to form a gating unit, and the nanoparticles to be tested are added to the liquid-based confined porous material. The electrostatic interaction between the ionic surfactant in the liquid-based confined porous material and the nanoparticles to be tested is used to increase or decrease the pressure threshold of the transport fluid through the gating unit; the surface charge properties of the nanoparticles to be tested are determined by measuring the change in the pressure threshold, and the charge of the nanoparticles to be tested is obtained by a linear fitting method.
2. The method for detecting surface charge of nanoparticles based on electrostatic interaction according to claim 1, characterized in that: The ionic surfactant solution includes a cationic surfactant, an anionic surfactant, an aqueous solution of amphoteric ionic surfactant, and a responsive ionic surfactant, and the concentration range is 0.1-2CMC.
3. The method for detecting surface charge of nanoparticles based on electrostatic interaction according to claim 1, characterized in that: The porous material comprises one of a nylon porous membrane, a water-based mixed cellulose membrane, a polytetrafluoroethylene membrane, a polyvinylidene fluoride membrane, a porous glass membrane, and a metal porous membrane, and the pore size of the pores ranges from 5 to 50 μm.
4. The method for detecting surface charge of nanoparticles based on electrostatic interaction according to claim 1, characterized in that: The nanoparticles to be tested are hydrophilic nanoparticles, including silicon dioxide, aluminum oxide, cerium dioxide, and silicon carbide.
5. The method for detecting surface charge of nanoparticles based on electrostatic interaction according to claim 1, characterized in that: The nanoparticles to be tested use a polar solvent as a dispersion medium to form a solution to be tested, and the mass fraction of the nanoparticles in the solution to be tested ranges from 0.01 to 1.0 wt.%.
6. The method for detecting surface charge of nanoparticles based on electrostatic interaction according to claim 1, characterized in that: The electrostatic interaction includes changes in surface tension, surface wettability, surface charge, pH value, viscosity or composition caused by charge exchange of substances at the contact interface.
7. The method for detecting surface charge of nanoparticles based on electrostatic interaction according to claim 1, characterized in that: The transport fluid is a gas, including air, oxygen, nitrogen, argon, carbon dioxide or carbon monoxide.
8. The method for detecting surface charge of nanoparticles based on electrostatic interaction according to claim 1, characterized in that: When the pressure threshold increases, the surface of the nanoparticle to be tested is judged to be negatively charged, and the linear model "charge = -21.01 (±1.15) △P-6.56 (±1.15)" is used to calculate the negative charge, where △P is the change in the transmembrane pressure threshold.
9. The method for detecting surface charge of nanoparticles based on electrostatic interaction according to claim 1, characterized in that: When the pressure threshold is lowered, the surface of the nanoparticle to be tested is judged to be positively charged, and the linear model "charge = -61.54 (±2.44) △P + 2.10 (±1.23)" is used to calculate the positive charge, where △P is the change in the transmembrane pressure threshold.
10. The method for detecting surface charge of nanoparticles based on electrostatic interaction according to claim 1, characterized in that: A detection system is used; the detection system includes a gas input channel, a gating unit, a gas output channel and a particle detection unit; the gating unit is arranged between the gas input channel and the gas output channel, the gating unit is provided with a chamber, the liquid-based confined porous material is encapsulated in the chamber, and the chamber is provided with a channel for injecting liquid to be tested; the particle detection unit includes a pressure sensor and a data conversion system, the pressure sensor is used to collect pressure information and input it into the data conversion system, and the data conversion system converts the pressure information and its change value into charge information on the surface of the nanoparticles.
